Technologies éducatives et développement : une brève histoire de la télévision scolaire au Niger - Gado ALZOUMA (Tic & Société)
The history of development in Africa is littered with all sorts of experiments and projects centred on new technologies often presented as a panacea to the problems of health, education, or agricultural production. The failure of some of those projects shows the limits of the technocentrist approach which has recently resurfaced in the developmentalist discourse and which is based on the idea that technology (and technology alone) can solve all the social and economic problems Africa is facing. This is the case of the educational television in Niger that was supposed to ensure a rapid access to universal education. It started in 1964 and was abandoned in 1979. It failed to transform the educational system in any significant way, the school enrolment rate in Niger still being under 60 %, 46 years after the experiment started. In this paper, I intend to show that this failure was not due to a lack of community involvement as generally advanced by project evaluations, but the result of a confrontation of divergent views of the world and society. Indeed, the educational television has become an issue of both social and political struggle, which resulted in the victory of one of the parties and the allocation of the educational television to other purposes for which it was not previously designed.